Estimated cumulative incidence of intervention by children’s social care services to age 18: a whole-of-England administrative data cohort study using the child in need census - Jay, Matthew A; Troncoso, Patricio; Bilson, Andy; Thomson, Dave; Dorsett, Richard; Pearson, Rachel; De Stavola, Bianca; Gilbert, Ruth (International Journal of Population Data Science, 2025)
Introduction Each year, children's social care (CSC) recognises around 3% of all children as children in need (CiN) of intervention, including those who receive a child protection plan due to risks of substantial harm and those who become looked after in state care. A previous cumulative estimate of the incidence of becoming CiN of 14% to age 5 indicates that the childhood lifetime incidence is likely very high. Objectives We aimed to estimate the cumulative incidence of referrals, social work assessments, being recognised as a CiN or made subject to a child protection plan (CPP) before age 18 in England. Methods The annual CiN census contains all-of-England longitudinal records of CSC referrals. Data collection began in 2008, meaning there is no cohort that can be followed up from birth to age 17 (i.e., before 18th birthday). Analyses revealed data quality issues before 2011/12. We estimated the above cumulative incidences in three cohorts and combined them, adjusting numerators to account for left-censoring. The three cohorts were children born in: (a) 2012/13, followed to age 5; (b) 2005/06, followed from age 6 age to 12; and (c) 2000/01, followed from age 13 to 17. We carried out sensitivity analyses to address possible bias induced by linkage error using one of two encrypted identifiers in the dataset. Results Of all children living in England, before turning 18, 35.4% were referred, 32.3% were assessed, 25.3% were recorded as CiN and 6.9% were subject to a CPP (37.5%, 34.6%, 26.0% and 7.1%, respectively, in sensitivity analyses). Conclusions By age 18, an estimated 1 in 4 children are identified by CSC as needing support at some point. Government should monitor the cumulative incidence of ever receiving CSC support with a view to addressing upstream health and social determinants.